(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2024)
Esophageal atresia is one of the most common congenital malformations requiring surgical management in the newborn period. The first successful primary repair was done in 1941. Since then, with the advances in medical and surgical aspects of management, the survival rates have shown drastic improvement even in resource challenged areas. Early diagnosis, appropriate perioperative management, and regular follow-up are key to reducing disease-related morbidity and improving the quality of life in these children. This review is an attempt to highlight the etiopathogenesis of the anomaly and to sensitize the readers about the association of various other congenital malformations with EA/TEF in addition to the surgical management of the disease. Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 49-61